Periodic motion-based visual stimulus - Wilson, Andrew D.; Tashev, Ivan; Gamper, Hannes; Cutrell, Ed; Johnston, David; Emmanouilidou, Dimitra (Microsoft, 2022)
Description A computer device is provided that includes a display device, and a sensor system configured to be mounted adjacent to a user's head and to measure an electrical potential near one or more electrodes of the sensor system. The computer device further includes a processor configured to present a periodic motion-based visual stimulus having a changing motion that is frequency-modulated for a target frequency or code-modulated for a target code, detect changes in the electrical potential via the one or more electrodes, identify a corresponding visual evoked potential feature in the detected changes in electrical potential that corresponds to the periodic motion-based visual stimulus, and recognize a user input to the computing device based on identifying the corresponding visual evoked potential feature. Inventors Andrew D Wilson, Hakim SI MOHAMMED, Christian Holz, Adrian Kuo Ching Lee, Ivan Jelev Tashev, Hannes Gamper, Edward Bryan Cutrell, David Emerson Johnston, Dimitra Emmanouilidou, Mihai R Jalobeanu Access Patent Public Search Basic | USPTO
US-20220365599-A1